Infection prevention and control in daycare centers—a survey of caregivers’ knowledge and practices in Ogbomoso Community, Southwest Nigeria - Ishola, Rafiat Omotayo; Ajala, Dolapo Emmanuel; Olayanju, Grace; Ilugbaro, Deborah Oluwadamilola; Ajala, Ronke Gbonjubola; Dosumu, Taiwo Omotayo; Ogunmodede, Eunice Oluwakemi (Frontiers in Public Health, 2025)
IntroductionInfectious diseases can spread rapidly among children in daycare centers (DCC). Caregivers at DCC play a crucial role in preventing and controlling these diseases.ObjectiveThis study aimed to assess the knowledge and practice of infection prevention and control (IPC) among caregivers in DCC.MethodsA descriptive cross-sectional study was conducted involving daycare caregivers in the Ogbomoso community, Southwest Nigeria. The Taro Yamane formula was used to calculate a minimum sample size of 111 caregivers from a total population of 136. Due to the lack of a formal registry for daycare centers, the snowball sampling technique was employed; initial participants referred additional caregivers from their professional networks, which aided in recruiting this hard-to-reach population. A pretested, self-developed questionnaire, with a Cronbach’s alpha coefficient of 0.96, was administered. Data were analyzed using descriptive and inferential statistics (α = 0.05).ResultsThe findings from this study showed that the majority (60%) of the respondents were within the age group of 30–39 years. Overall, 40% of the respondents had good knowledge of IPC, while 47.3% exhibited poor practices related to IPC. Years of experience (p = 0.001) and knowledge (p = 0.000) were statistically significant with the practice of IPC.ConclusionThis study identified a significant association between caregivers’ knowledge and their practice of infection prevention and control (IPC), as well as between years of experience and IPC practice. We recommend implementing regular, targeted IPC training that specifically addresses the identified gaps in practice, particularly in hand hygiene and waste management, to further improve infection control standards in daycare centers.